Autoimmune Hepatitis after Ten Years from Pegylated Interferon Treatment- A Case Report - C, Elia; V, Boano; E, Battaglia; M, Grassini (Archives of Clinical and Medical Case Reports, 2020)
Interferon is an effective therapy in several diseases; it was a milestone of hepatitis c treatment for a long time. Pegylated interferon is more effective than alpha interferon, adding polyethylene glycol. It has an immunomodulatory effect through the antiviral and cellular activity, but it is burden with adverse effects, some of them are serious. It can be explain with the immunological role of interferon and it is derived in the genesis of some disease like autoimmune hepatitis, it is a liver disease with a multifactorial genesis, an environment agent can stimulate the predisposed subject. We present a case of autoimmune hepatitis ten years later than pegylated interferon therapy.